Răspunsuri

2014-09-28T18:45:46+03:00
1. a. (3x²+2x-1)-(x²-x+3 ) (-2x² + x + 4) =3x²+2x-1-(-2xla puterea 4+x la a treia+4x²+2xla atreia-x²-4x-6x²+3x+12)=3x²+2x-1-(-2xla a patra+3x la a treia-3x²-x+12)=3x²+2x-1+2xla a patra-3x la a treia+3x²+x-12=2x la a patra-3x la atreia+6x²+3x-13=x²(2x²-3x+6)+3x-13
b. (a²+b²-2ab)-(a2+c²-2ac)-(b²+c²-2bc) =a²+b²-2ab-a²-c²+2ac-b²-c²+2bc=a²-a²+b²-b²-c²-c²-2ab+2ac+2bc=-2c+2bc-2ab+2ac=2c(b-c)-2a(b-c)=2(b-c)(c-a)
2.a-[b-(c-d)] =a-(b-c+d)=a-b+c-d
x-[y-(-3x+y-5)]+5-4x=x-(y+3x-y+5)+5-4x=x-y-3x+y-5+5-4x=-6x
2 5 2